Metabolomic and transcriptomic analyses of the flavonoid biosynthetic pathway in blueberry (Vaccinium spp.) - Li, Yinping; Li, Haifei; Wang, Shiyao; Li, Jing; Bacha, Syed Asim Shah; Xu, Guofeng; Li, Jing (Frontiers in Plant Science, 2023)
As a highly economic small fruit crop, blueberry is enjoyed by most people in terms of color, taste, and rich nutrition. To better understand its coloring mechanism on the process of ripening, an integrative analysis of the metabolome and transcriptome profiles was performed in three blueberry varieties at three developmental stages. In this study, 41 flavonoid metabolites closely related to the coloring in blueberry samples were analyzed. It turned out that the most differential metabolites in the ripening processes were delphinidin-3-O-arabinoside (dpara), peonidin-3-O-glucoside (pnglu), and delphinidin-3-O-galactoside (dpgal), while the most differential metabolites among different varieties were flavonols. Furthermore, to obtain more accurate and comprehensive transcripts of blueberry during the developmental stages, PacBio and Illumina sequencing technology were combined to obtain the transcriptome of the blueberry variety Misty, for the very first time. Finally, by applying the gene coexpression network analysis, the darkviolet and bisque4 modules related to flavonoid synthesis were determined, and the key genes related to two flavonoid 3′, 5′-hydroxylase (F3′5′H) genes in the darkviolet module and one bHLH transcription factor in the bisque4 module were predicted. It is believed that our findings could provide valuable information for the future study on the molecular mechanism of flavonoid metabolites and flavonoid synthesis pathways in blueberries.